Peran Allium sativum dalam menanggulangi patogen rongga mulut - Utomo, Bella; Aryani Hayuningtyas, Ria; Nugrogo, Didi (Jurnal Kedokteran Gigi Terpadu, 2024)
Allium sativum is known as a bulbous plant that is produced all over the world. Apart from being used as a cooking spice, Allium sativum is acknowledged to have a variety of medical benefits, especially in terms of its antibacterial properties. The active compounds that contribute to its antibacterial effect, such as allicin, alliin, ajoene, flavonoids, saponins, tannins, steroids, and triterpenoids, work together to overcome various types of microorganisms, including Gram-positive and Gram-negative bacteria. Allium sativum extract has been demonstrated in numerous studies to have strong antibacterial activity, indicating that it can be used as a natural remedy for oral health issues.